2011
DOI: 10.1016/j.neuron.2011.06.039
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptomic Atlas of Mouse Neocortical Layers

Abstract: SummaryIn the mammalian cortex, neurons and glia form a patterned structure across six layers whose complex cytoarchitectonic arrangement is likely to contribute to cognition. We sequenced transcriptomes from layers 1-6b of different areas (primary and secondary) of the adult (postnatal day 56) mouse somatosensory cortex to understand the transcriptional levels and functional repertoires of coding and noncoding loci for cells constituting these layers. A total of 5,835 protein-coding genes and 66 noncoding RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
243
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 271 publications
(253 citation statements)
references
References 72 publications
9
243
0
1
Order By: Relevance
“…Mouse lncRNAs were identified by updating and extending the method outlined in Clark et al (2012). Mouse RNAs were obtained from the following sources: the UCSC mm9 mRNA track (alignments between GenBank RNAs and the genome), UCSC genes (predictions based on RefSeq, GenBank, and the tRNA Genes track) (Kent et al 2002), and RefSeq genes (Pruitt et al 2012) (downloaded April 10, 2012); also included were lincRNAs identified in Belgard et al (2011), transcripts overlapping novel lincRNA loci identified in Guttman et al (2010), and transcripts overlapping lincRNA loci investigated by Guttman et al (2011).…”
Section: Lncrna Capture Designmentioning
confidence: 99%
“…Mouse lncRNAs were identified by updating and extending the method outlined in Clark et al (2012). Mouse RNAs were obtained from the following sources: the UCSC mm9 mRNA track (alignments between GenBank RNAs and the genome), UCSC genes (predictions based on RefSeq, GenBank, and the tRNA Genes track) (Kent et al 2002), and RefSeq genes (Pruitt et al 2012) (downloaded April 10, 2012); also included were lincRNAs identified in Belgard et al (2011), transcripts overlapping novel lincRNA loci identified in Guttman et al (2010), and transcripts overlapping lincRNA loci investigated by Guttman et al (2011).…”
Section: Lncrna Capture Designmentioning
confidence: 99%
“…In the human cortex we observed that subplate subpopulations show increased compartmentalization and that these segregate into sublayers (Hoerder‐Suabedissen and Molnár, 2015). In the adult brain, Belgard et al (2011) produced the first transcriptomic atlas of the mouse cortical layers and provided a transcriptomic comparative gene expression analysis to obtain expression profiles of 5,130 highly transcribed genes (Belgard et al, 2013) in a set of structures that develop from one of four sectors of the pallium (medial, dorsal, lateral, and ventral) in the adult mouse and chicken brain. This recent large‐scale transcriptomic analysis reveals expression similarity across chicken and mouse between homologous telencephalic structures such as striatum and hippocampus, but a mostly divergent pattern in other telencephalic compartments (Belgard et al, 2013; Fig.…”
Section: Exploring Brain Evolution From Transcriptome Databasesmentioning
confidence: 99%
“…Electrophysiologically, cortical lamina have since long been shown to display distinct phenotypes in cortical map plasticity (Diamond et al, 1994), stemming from the organization of their thalamic and cortical inputs and their cellular populations (Molyneaux et al, 2007). Cortical laminae can be readily identified through molecular markers, showing their distinct molecular identities (Belgard et al, 2011;Molyneaux et al, 2007), which likely shows the coherence between a layer's functional role and the molecules required to exert it. This stresses the importance of anatomical resolution when studying experiencedependent plasticity on either the electrophysiological and molecular level.…”
Section: ) From Synaptic Plasticity To Synaptic Disordersmentioning
confidence: 99%